Heterologous Caseins: The Role of Phosphorylation in Their Functionality and How to Achieve It - Soledad Mora Vásquez; Santiago García-Jacobo; Guy A. Cardineau; Silverio García-Lara (Biomolecules)
Heterologous expression of caseins in non-mammalian systems offers a sustainable and scalable alternative for producing milk proteins, with potential applications in the food and biopharmaceutical industries. However, a significant challenge in these systems is achieving proper phosphorylation, a critical post-translational modification required for casein functionality and stability. This review explores the current state of research on heterologous casein production, with a particular focus on the biological and technical hurdles associated with phosphorylation. Specifically, we examine the absence of the mammalian-specific kinase Fam20C in plant and yeast systems and the broader lack of secretory kinase machinery in bacteria, which collectively contribute to impaired phosphorylation fidelity. While some endogenous kinases may partially compensate, they are typically insufficient to replicate the phosphorylation pattern required for functionality. We evaluate potential strategies to address these limitations, analyze the role of phosphorylation in casein functionality, provide insights into existing patents and experimental approaches, and highlight ongoing research efforts. By synthesizing current knowledge and proposing new avenues for innovation, this review aims to provide a roadmap for the successful production of functional heterologous caseins.